A new insular species of Begonia (Begoniaceae) from São Paulo State, Brazil - Miranda, Marcelo Dias (Phytotaxa, 2023)
Begonia schizostya, a new species of Begonia sect. Astrothrix from São Paulo state, Brazil is described. Begonia schizostyla is morphologically similar to Begonia bullatifolia and Begonia crispula, with which it is compared. The new species grows in Ombrophilous Dense Submontane Forest, over rocks inside the primary forest of São Sebastião Island. Description, comparisons with related species, etymology, taxonomic comments, illustration and localization map of the new species are provided.